Ciris 118: an Emendation - Kayachev, Boris (Polskie Towarzystwo Filologiczne, 2018)
The paper argues that Ciris 118 should be restored as “reicere [Heinsius: dicere HAR: ducere ρ: deicere Vollmer] et indomita [ρ: indomitas HAR] uirtute retundere Minon [scripsi:mentes HARρ]”
Keywords: Ciris; Vergil